Neutrophil extracellular traposis in cancer patients with acute ischemic stroke. - Jae-Won Hyun; Rosah May Palermo Payumo; Jieun Chung; You-Ri Kang; Su-Hyun Kim; Ho Jin Kim; Ji-Youn Han; Sang-Yoon Park (PLoS ONE)
Background Patients with cancer exhibit an increased risk of acute ischemic stroke (AIS), and neutrophil extracellular traposis (NETosis) has been proposed as a mechanism underlying cancer-associated hypercoagulability. However, studies validating these findings in independent cohorts are limited. Objective We sought to explore whether NETosis-associated markers (plasma DNA and nucleosomes) are increased in patients with active cancer and AIS, and whether these increases correlate with coagulopathy markers in cancer patients. Methods We analyzed NETosis-associated markers in cancer patients with and without AIS and healthy controls, and assessed the correlation between these markers and coagulopathy markers. Additionally, we compared the levels of Netosis-associated markers between cancer patients with conventional stroke mechanisms (CSM) and those with embolic stroke of undetermined source (ESUS). Results Plasma DNA and nucleosome levels were significantly higher in cancer patients with AIS than in cancer controls and healthy controls (p < 0.001, respectively). Both markers correlated with D-dimer levels in cancer patients with AIS. In a sub-analysis, cancer patients with ESUS showed higher levels of NETosis-associated markers compared to those with CSM, whereas vascular risk factors were more frequently observed in cancer patients with CSM. Conclusion These findings suggest that NETosis may contribute to hypercoagulability in patients with active cancer and AIS, particularly in those with ESUS. These results provide additional evidence supporting the establishment of pathophysiology-based therapeutic approaches.